RNF40 epigenetically modulates glycolysis to support the aggressiveness of basal-like breast cancer - Prokakis, Evangelos; Jansari, Shaishavi; Boshnakovska, Angela; Wiese, Maria; Kusch, Kathrin; Kramm, Christof; Dullin, Christian; Rehling, Peter; Glatzel, Markus; Pantel, Klaus; Wikman, Harriet; Johnsen, Steven A.; et al. (Cell death & disease, 2023)
Triple-negative breast cancer (TNBC) is the most difficult breast cancer subtype to treat due to the lack of targeted therapies. Cancer stem cells (CSCs) are strongly enriched in TNBC lesions and are responsible for the rapid development of chemotherapy resistance and metastasis. Ubiquitin-based epigenetic circuits are heavily exploited by CSCs to regulate gene transcription and ultimately sustain their aggressive behavior. Therefore, therapeutic targeting of these ubiquitin-driven dependencies may reprogram the transcription of CSC and render them more sensitive to standard therapies. In this work, we identified the Ring Finger Protein 40 (RNF40) monoubiquitinating histone 2B at lysine 120 (H2Bub1) as an indispensable E3 ligase for sustaining the stem-cell-like features of the growing mammary gland. In addition, we found that the RNF40/H2Bub1-axis promotes the CSC properties and drug-tolerant state by supporting the glycolytic program and promoting pro-tumorigenic YAP1-signaling in TNBC. Collectively, this study unveils a novel tumor-supportive role of RNF40 and underpins its high therapeutic value to combat the malignant behavior of TNBC.
Veröffentlicht: 28. September 2023
Gesehen am 04.01.2024